2022
DOI: 10.3389/fonc.2022.1044344
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based prognostic model of Chinese medicine affecting the recurrence and metastasis of I-III stage colorectal cancer: A retrospective study in China

Abstract: BackgroundTo construct prognostic model of colorectal cancer (CRC) recurrence and metastasis (R&M) with traditional Chinese medicine (TCM) factors based on different machine learning (ML) methods. Aiming to offset the defects in the existing model lacking TCM factors.MethodsPatients with stage I-III CRC after radical resection were included as the model data set. The training set and the internal verification set were randomly divided at a ratio of 7: 3 by the “set aside method”. The average performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the Yiqi Sanjie (YQSJ) formula has demonstrated clinical efficacy in the treatment of stage III CRC, with studies illustrating its role in modulating molecular and microbiota changes in CRC tissues and cell lines, thereby suggesting new potential therapeutic targets in CRC 12 . Moreover, the integration of TCM factors in prognostic models, leveraging machine learning methods, has shown promise in predicting the recurrence and metastasis in stage I‐III CRC patients, thereby offering a novel approach in the clinical management of CRC 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the Yiqi Sanjie (YQSJ) formula has demonstrated clinical efficacy in the treatment of stage III CRC, with studies illustrating its role in modulating molecular and microbiota changes in CRC tissues and cell lines, thereby suggesting new potential therapeutic targets in CRC 12 . Moreover, the integration of TCM factors in prognostic models, leveraging machine learning methods, has shown promise in predicting the recurrence and metastasis in stage I‐III CRC patients, thereby offering a novel approach in the clinical management of CRC 15 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Moreover, the integration of TCM factors in prognostic models, leveraging machine learning methods, has shown promise in predicting the recurrence and metastasis in stage I‐III CRC patients, thereby offering a novel approach in the clinical management of CRC. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning has recently been successfully applied in disease treatment and effect evaluation of TCM, such as in prescription recommendation, transition prediction, and treatment prognosis (Table 2 ). The treatment prognosis model has received increasing attention in the context of clinical diagnosis and treatment decision-making [ 84 ]. Zhang [ 85 ] utilized transformer and GAN to develop an auxiliary tool to prescribe TCM prescriptions based on the patient’s clinical electronic health records.…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%
“…SVM classification revealed significant white matter network alterations after treatment in the drug groups, with an accuracy of 68.18%. Tang [ 84 ] used RF, SVM, logistic regression, and extreme gradient boosting to predict whether colorectal cancer recurrence and metastasis with TCM factors would occur within 3 years and 5 years after radical surgery. The results showed that the four methods all showed certain predictive ability (area under the curve values > 0.70).…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%